PENGUKURAN DAN PERBAIKAN KINERJA RANTAI PASOK UKM LAPIS BOGOR SANGKURIANG UNTUK MENINGKATKAN DAYA SAING UKM - Fatimatuzzahro Diah PD, Rizal Syarief, dan Marimin (Jurnal Teknologi Industri Pertanian, 2016)
Nowaday, the rate of growth and development small medium enterprise (SME)is in line with increasing enterprise competition. In modern competition today is focusing not only with other company, but also become the competition against supply chain. Therefore, the enterpreneurs have to prepare strategies to fix supply chain for increase SME competitiveness. Lapis Bogor Sangkuriang (LBS) becoming the first inovative of taro sponge cake which is known as signature snack in Bogor. This research aimed to identified supply chain condition, measured supply chain performance based Supply Chain Operation Reference (SCOR) and chosed the priority strategy to improve the supply chain condition with Technique Order Preference Similiarity to Ideal Solutions (TOPSIS). The supply chain pattern of Lapis Bogor Sangkuriang (LBS) consisted of direct supply from supplier to manifacture of LBS and indirect supply or through the cooperative. The supply chain measurement in LBS used SCOR and combined with Analytical Hierarchy Process (AHP) produced the performance scor of 68.5% with the matrix SCORs that had to be improve were upside supply chain adaptability (26.6%) and flexibility (37.5%). The priority strategy to improve the supply chain performance based on TOPSIS was increasing machine and labour productivity.Keywords:competitiveness, improvement, measurement, small medium enterprise, supply chain